Teachers’ and students’ perceptions of the role of practical work in science - Bingley, Stacie (2016)
This study takes place in a large, mixed, 11-18 school in the Midlands. In recent years, within the College, there has been a perceived augmentation of a culture of reluctance and lethargy towards practical work in science amongst the students. Teachers have reported that many students were trying to choose to ‘opt out’ of practical work and instead work out of a text book. The aim of this study was to explore these attitudes and opinions towards practical work in science and to identify any correlation in the underlying reasons for the perspectives displayed. After reviewing current literature about the topic, it became apparent that there was very little research conducted into the perspective of the student with regards to the purpose of practical work in science and how that compared to the perspective and intentions of the teacher. As the emphasis on practical work has been heightened during the A-Level reform, this investigation had clear justification. In order to explore these perspectives, four Research Questions were composed. Firstly, what do students and teachers believe is the purpose of practical work in science? Secondly, do all students consider practical work in science enjoyable and beneficial to their learning? Thirdly, what elements of practical work are considered to be the most important? Lastly, do students always understand what a practical requires of them? A ‘mixed method’ research style was used, which incorporated quantitative results from 14 science teacher questionnaires and 764 student questionnaires with the qualitative data collected from a semi structured interview with a focus group of eight students from a range of different year groups. Results showed that 50% of all students that responded to the questionnaire had the same viewpoint about the role of practical work in science, however, there was a concerning 6% that stated they didn’t know the purpose. The reasons behind the disinterest and non-enjoyment were surprising and rectifiable.